1995
DOI: 10.1002/j.1537-2197.1995.tb12644.x
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Analysis of Crop Rotation Effects on Weed Seedbanks

Abstract: A population-projection model was developed for a depth-structured weed seed population (employing tywsition matrices to model seed survival, germination, and vertical movement) and plant survival and seed production. Abutflon theophrasti and Setaria viridis seedbank dynamics were simulated in continuous com and in two crop rotations (com-soybean and oatl clover-com-soybean-com). Results suggest that crop rotation can nearly eliminate S. viridis seedbanks, while A. theophrasti seedbanks are less affected. Sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 15 publications
0
53
0
Order By: Relevance
“…Periodic models explicitly account for variations in life stage transition probabilities in a sequence of environments that repeats itself over time (Caswell and Trevisan 1994). Periodicmatrix models have been used previously in the weed science literature to understand the effect of management within the sequence of environments arising from progression of crops within a crop rotation (Jordan et al 1995, Mertens et al 2002. Our model followed S. faberi demography through four subannual periods in each of the phases in the wheat-corn-soybean crop sequence, for a total of 12 periods in one rotation cycle (Fig.…”
Section: Periodic Matrix Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Periodic models explicitly account for variations in life stage transition probabilities in a sequence of environments that repeats itself over time (Caswell and Trevisan 1994). Periodicmatrix models have been used previously in the weed science literature to understand the effect of management within the sequence of environments arising from progression of crops within a crop rotation (Jordan et al 1995, Mertens et al 2002. Our model followed S. faberi demography through four subannual periods in each of the phases in the wheat-corn-soybean crop sequence, for a total of 12 periods in one rotation cycle (Fig.…”
Section: Periodic Matrix Modelmentioning
confidence: 99%
“…Mature Setaria faberi (giant foxtail) panicles in corn in Boone, Iowa, USA, in September 2001. Photo credit: Adam Davis. been applied less often to weed management questions (Jordan et al 1995, Pino et al 1998, Shea and Kelly 1998, McEvoy and Coombs 1999, Mertens et al 2002. One of the clear benefits of applying matrix simulation models to problems in ecological weed management is the ability of such models to integrate the effects of multiple management tactics upon different life stage transitions so that weed population growth may be observed as an emergent property of management practices.…”
Section: Introductionmentioning
confidence: 99%
“…The periodic matrix modeling approach has been used previously to simulate weed population dynamics in crop rotations (Jordan et al 1995;Ullrich 2000;.…”
Section: N+y = (B(y|)b(i)b (M )B(/+i)b(/))n A= 1 [ 2 ]mentioning
confidence: 99%
“…Jordan et al (1995) found that X was most sensitive to changes in overwinter seedbank decline in the upper 10 cm of soil. By identifying overwinter seedbank decline as a parameter with the potential to greatly influence X, this analysis suggested that overwinter seedbank decline represents a weed management "choke point" (i.e., a stage in the weed life cycle where management interventions may be applied with the greatest likelihood of reducing X).…”
Section: N+y = (B(y|)b(i)b (M )B(/+i)b(/))n A= 1 [ 2 ]mentioning
confidence: 99%
See 1 more Smart Citation